Evaluating facility‐based antiretroviral therapy programme effectiveness: a pilot study comparing viral load suppression and retention rates. Issue 6 (20th April 2016) - Duber, Herbert C.; Roberts, D. Allen; Ikilezi, Gloria; Fullman, Nancy; Gasasira, Anne; Gakidou, Emmanuela; Haakenstad, Annie; J. Levine, Aubrey; Achan, Jane
Abstract: Objectives: Increased demand for antiretroviral therapy (ART) services combined with plateaued levels of development assistance for HIV/AIDS requires that national ART programmes monitor programme effectiveness. In this pilot study, we compared commonly utilised performance metrics of 12‐ and 24‐month retention with rates of viral load (VL) suppression at 15 health facilities in Uganda. Methods: Retrospective chart review from which 12‐ and 24‐month retention rates were estimated, and parallel HIV RNA VL testing on consecutive adult patients who presented to clinics and had been on ART for a minimum of six months. Rates of VL suppression were then calculated at each facility and compared to retention rates to assess the correlation between performance metrics. Multilevel logistic regression models predicting VL suppression and 12‐ and 24‐month retention were constructed to estimate facility effects. Results: We collected VL samples from 2961 patients and found that 88% had a VL ≤1000 copies/ml. Facility rates of VL suppression varied between 77% and 96%. When controlling for patient mix, a significant variation in facility performance persisted. Retention rates at 12 and 24 months were 91% and 79%, respectively, with a comparable facility‐level variation. However, neither 12‐month ( ρ = 0.16) nor 24‐month ( ρ = −0.19) retention rates were correlated with facility rates of VL suppression. Conclusions: Retaining patients in care and suppressing VL are both critical outcomes. Given the lack of correlation noted in this study, the utilisation of VL monitoring may be necessary to truly assess the effectiveness of health facilities delivering ART services.